1993
DOI: 10.1121/1.405815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cognitive workload on speech production: Acoustic analyses and perceptual consequences

Abstract: The present investigation examined the effects of cognitive workload on speech production. Workload was manipulated by having talkers perform a compensatory visual tracking task while speaking test sentences of the form "Say hVd again." Acoustic measurements were made to compare utterances produced under workload with the same utterances produced in a control condition. In the workload condition, some talkers produced utterances with increased amplitude and amplitude variability, decreased spectral tilt and F0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 28 publications
3
64
1
1
Order By: Relevance
“…These studies, and many others, have provided a great deal of new information about the way in which individual talkers modify and adjust their articulatory patterns to accommodate situational demands. However, aside from establishing that the "clear" speech style does indeed provide an intelligibility advantage over "conversational" speech (Picheny et al, 1985), considerably less attention has been paid to the direct perceptual consequences, from the listener's point of view, of different styles of speech (see Summers et al, 1988;Lively et al, 1993). Important questions that remain to be answered are: (1) Which of the clear speech transformations are most effective in aiding speech communication?…”
Section: Introductionmentioning
confidence: 99%
“…These studies, and many others, have provided a great deal of new information about the way in which individual talkers modify and adjust their articulatory patterns to accommodate situational demands. However, aside from establishing that the "clear" speech style does indeed provide an intelligibility advantage over "conversational" speech (Picheny et al, 1985), considerably less attention has been paid to the direct perceptual consequences, from the listener's point of view, of different styles of speech (see Summers et al, 1988;Lively et al, 1993). Important questions that remain to be answered are: (1) Which of the clear speech transformations are most effective in aiding speech communication?…”
Section: Introductionmentioning
confidence: 99%
“…Even young preschool children actively adapt their speech to accommodate perceived listener characteristics (Shatz and Gelman, 1973). Systematic speech modifications also have been observed in noisy environments (Hanley and Steer, 1949;Junqua, 1993;Schulman, 1989;Summers et al, 19881, in environments involving heavy workload or that precipitate psychological stress (Brenner et al, 1985;Lively et al, 1993;Tolkmitt and Scherer, 1986;Williams and Stevens, 19691, and when speakers are asked to "speak clearly" in laboratory settings Butterfield, 1990, 1991;Moon, 1991;Moon and Lindblom, 1994).…”
Section: Speech Adaptations To Risk Populationsmentioning
confidence: 99%
“…In addition, the adaptations observed in Lombard speech have sometimes included variability due to gender effects (Junqua, 1993). Under conditions of high workload, speakers typically increase both amplitude and variability in amplitude, while simultaneously speaking at a faster rate and with decreased pitch range (Lively et al, 1993). When speakers are stressed by their environment, noteworthy adaptations include an increase in fundamental frequency and change in pitch variability (Brenner et al, 1985;To&mitt and Scherer, 1986;Williams and Stevens, 1969).…”
Section: Speech Adaptations In Adverse Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies have suggested that increased disfluency rate may be due to coordination processes rather than planning difficulties associated with workload (Swerts, 1998;Bortfeld et al, 2001;Clark and Krych, 2004). In terms of speech, Lively et al (1993) found that utterance length decreases with workload, but more recent work by Khawaja et al (2012) found increases in sentence length as well as in speech rate, words indicating disagreement, and the usage of plural personal pronouns (e.g., "we" and "us"). Finally, Urban et al (1995) found that under high workload, effective teams asked fewer questions, made fewer requests, and made fewer responses to requests.…”
mentioning
confidence: 99%